Hybrid immersive three-dimensional sound reproduction system with steerable parametric loudspeakers - Gan, Woon-Seng (2013)
A loudspeaker must be both dispersive and directive to accurately reproduce spatial audio from digital media. To address this problem, an audio system that has a unique combination of conventional and parametric loudspeakers has previously been proposed and proved to be effective in producing an immersive 3D soundscape. However, this system has two drawbacks: (1) There is only one fixed "sweet spot", and (2) only one listener within the "sweet spot" can enjoy the complete experience. Therefore, a hybrid 3D sound reproduction system combining conventional loudspeakers with a pair of steerable parametric loudspeakers is proposed in this paper. By using this new combination of conventional and steerable parametric loudspeakers, the "sweet spot" can be steered towards the listener's head position. Thus, the listener no longer needs to keep his head stationary while watching movies or playing games, which resulting in a more relaxing and pleasant experience. Furthermore, a dual-beamsteering method is proposed for the parametric loudspeaker, which provides a flexible software-control solution to allow the 3D sound experience to be enjoyed by two listeners simultaneously. This paper provides the system overview and highlights the key processing techniques in rendering a "steerable" immersive 3D soundscape.